Radiological frontiers in understanding paraspinal muscle pathophysiology in chronic low back pain - Li, Xuerou; Dong, Fuwen; Chen, Xiaofei; Luo, Xingxin; Wang, Wenqi (Frontiers in Medicine, 2025)
BackgroundParaspinal muscles have a profound role in maintaining spinal stability and are often implicated in spinal degenerative conditions as well as chronic low back pain (CLBP). Alterations in these muscles have significant clinical implications for early prevention, treatment strategies, prognosis, and understanding the underlying mechanisms of CLBP. Recent advances in imaging techniques can generate prominent structural and functional characteristics of these muscles.ObjectivesThis study is specifically to review recent advancements in imaging techniques focusing on the regenerative and degenerative properties pertinent to paraspinal muscles in the context of CLBP.MethodsA literature review was executed to ascertain the databases including PubMed, Google Scholar, RelMed, and the National Library of Medicine. The search included studies elucidating recent imaging advancements, fiber-type composition analysis, level/depth-specific muscle characteristics, and clinical applications of novel radiological techniques in evaluating paraspinal muscle morphology and function. We performed this review without comprehensive meta-analysis.ResultsThe review identified significant advancements in imaging modalities for assessing paraspinal muscles, including functional MRI (fMRI), quantitative MRI (qMRI), and T2 mapping techniques. Key findings include: Fiber-type composition analysis: Recent studies elucidate the role of depth-dependent fiber-type gradients along with their correlation with muscle function in health and disease. Standardized imaging protocols: The lack of uniform imaging protocols remains a challenge, emphasizing the need for standardization to improve reproducibility and reliability. Radiological advances: Emerging techniques such as advanced fMRI and qMRI enable detailed visualization of muscle structure and function, overcoming limitations of traditional imaging methods. Age-related microvascular changes: age-related microvascular alterations significantly impact paraspinal muscle morphology and can be effectively captured by modern imaging biomarkers.ConclusionAdvances in imaging techniques have enhanced our understanding of the structural and functional changes in paraspinal muscles associated with CLBP. The integration of imaging biomarkers into clinical practice holds promise for early diagnosis, targeted interventions, and better prognostic evaluations. Future research should focus on developing standardized imaging protocols and further exploring depth-specific properties of paraspinal muscles to enhance clinical outcomes.